Revealing the Fracklands: a framework for addressing the wicked problems of America’s hydraulic fracturing landscape - Lanning, Evan Klein (Kansas State University, 2018)
In recent decades, traditional methods of oil and gas extraction in the United States have been fortified by hydraulic fracturing, or fracking. The process of fracking involves injecting water, aggregates, and chemicals into the earth to rupture rock that is trapping oil and gas. This process has unlocked access to once unobtainable reserves, and as a result, U.S. oil and gas production has continued to increase despite recurring forecasts that supplies would peak. While increased production has strengthened some sectors in the U.S. economy, it has also renewed a reliance on non-renewable energy, compromised the well-being of communities, and poses serious environmental threat. While research into the process of hydraulic fracturing and its effects are common, little discussion has been generated regarding the broader impacts of the systems required to construct, supply, and maintain fracking operations. The processes of hydraulic fracturing contain a dense array of components that effect both the present and future state of communities, environments, and economies. As energy demands grow and resources deplete, these millions of facilities will demarcate the wicked problems of a post-oil and gas future and reveal a dense system of derelict infrastructure and underutilized lands. This report presents the Fracklands. Fracklands are a comprehensive telling of the landscapes of hydraulic fracturing. They offer insight into what a dynamic and complex system of modern oil and gas extraction infrastructure looks like. After first defining fracking and discussing current practices and policies as grounds, I present a classification framework for defining the Fracklands. Organized by four approaches – Systems, Typologies, Trends and Futures – this Framework utilizes a set of descriptive methods conducted in three U.S. regions to present and discuss the Fracklands. Results reveal a more complete picture of fracking’s effects on the American landscape today, while giving hints of what the Fracklands will present in the future. The Fracklands are a little understood system of components and processes that profoundly affect land, people, place, and society. By presenting the Fracklands framework in this report, I aspire that planners, designers, and decision-makers will have a clear outline for better understanding the nature of this wicked problem. As a point of departure, I propose three unique design-based alternatives to address the future of the Fracklands and dilemmas yet materialized. With the Fracklands revealed, footholds are set for a methodology to be adapted and used in future study for understanding the ever-changing landscape of hydraulic fracturing.
Keywords: Hydraulic fracturing; Wicked problems; Landscape classification; Visual storytelling; Mapping; Systems-based thinking